Efectos de un programa educativo lúdico en el mejoramiento de las habilidades motrices básicas en estudiantes de segundo grado de educación primaria de la Institución Educativa N° 60050 República de Venezuela, Iquitos 2023 - Navarro Cachique, Tania (2025)
The study’s main objective was to evaluate the effects of implementing a play based educational program on improving basic motor skills (BMS) in second grade elementary school students at Educational Institution No. 60050 “República de Venezuela,” Iquitos, during 2023; the play-based program was conducted over 12 weeks with structured play activities related to the dimensions of running, jumping, throwing, and rolling. In this regard, a quantitative, explanatory methodology with a pre-experimental design was employed, with a population of 63 students and a simple random sample of 29 students (16 in 2nd grade A and 13 in 2nd grade B). Thus, the results obtained thru inferential statistics using the Wilcoxon signed-rank test for related samples between the pre- and post-tests revealed a significant improvement with a significance level of 0.001 (p < 0.05). 0.001 (p < 0.05); these results support the affirmative hypothesis. For this reason, it is concluded that the playful educational program constitutes a highly effective and relevant pedagogical tool for stimulating basic motor skills in second-grade elementary school students.